2013
DOI: 10.1124/mol.113.088609
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Pharmacology of ABCG2 and Its Role in Chemoresistance

Abstract: The ATP-binding cassette, subfamily G, isoform 2 protein (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
175
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(178 citation statements)
references
References 157 publications
(181 reference statements)
3
175
0
Order By: Relevance
“…ABCG2 has been reported to mediate MDR by effluxing numerous agents, including mitoxantrone (MX), topotecan, irinotecan, DOX, nilotinib, and imatinib (16,(18)(19)(20). Indeed, upregulated expression of ABCG2 is observed in a variety of cancer stem cells, leading to the speculation that ABCG2 provides cellular protection against cytotoxic agents for cancer stem cells, which are inherently present in the cancer cell populations (21,22).…”
Section: Introductionmentioning
confidence: 99%
“…ABCG2 has been reported to mediate MDR by effluxing numerous agents, including mitoxantrone (MX), topotecan, irinotecan, DOX, nilotinib, and imatinib (16,(18)(19)(20). Indeed, upregulated expression of ABCG2 is observed in a variety of cancer stem cells, leading to the speculation that ABCG2 provides cellular protection against cytotoxic agents for cancer stem cells, which are inherently present in the cancer cell populations (21,22).…”
Section: Introductionmentioning
confidence: 99%
“…Other classes of anticancer drugs including vinblastine, cisplatin, and paclitaxel are not BCRP substrates (13). BCRP substrates are not limited to chemotherapeutics.…”
Section: Bcrp Substratesmentioning
confidence: 99%
“…BCRP substrates are not limited to chemotherapeutics. Drugs that have been shown to be BCRP substrates include, among others, prazosin, glyburide, cimetidine, sulfasalazine, and rosuvastatin (1,13). Nucleoside and nucleotide analogs such as AZT and lamivudine are also BCRP substrates (1).…”
Section: Bcrp Substratesmentioning
confidence: 99%
See 1 more Smart Citation
“…The ATP-binding cassette, subfamily G, isoform 2 protein (ABCG2) is a molecular determinant of the SP phenotype, and has been suggested to be involved in multidrug resistance in cancer. The ABCG2 acts as efflux proteins to transport a variety of molecules, including certain chemotherapeutic drugs [72] . Data suggested that ABCG2 is a promising molecular marker for identification of CSCs in tumors.…”
Section: Regulation Of Abcg2mentioning
confidence: 99%